Policy Shift to Reduce Unemployment of Vocational School Graduates in Indonesia (A National Study) - Eric Ohara; Slamet Prawiro Harto; Rita Fransina Maruanaya (Faculty of Engineering, Universitas Negeri Yogyakarta, 2020)
One of the enduring issues and problems in Indonesia is the link and match between vocational secondary schools and the world of work in terms of quantity, quality, location, and time. This research focuses on the first issue i.e. quantity of vocational secondary school graduates in terms of supply and demand. The objective of this research was to explore the proportion of general secondary and vocational secondary school students, to find out the unemployment rate of both school types, and to identify policy alternatives to reduce the unemployment rate of vocational secondary school graduates. To achieve the objective, a quantitative descriptive research method was adopted. The research found that the national average proportion of students from general secondary schools and vocational secondary schools was 62.92%:37.08% in 2016 and 63.39%:36.61% in 2019. The national average unemployment rate of both school graduates was 8.72% and 11.11%% respectively in 2016, and 7.92% and 10.42% respectively in 2019. Thus, the unemployment rate of vocational secondary school graduates was higher than those of general secondary school graduates. In Java Island, however, where the population is about 40% of the Indonesian total population, the percentage of vocational secondary students increases significantly from 44.34%:55.66% in 2016 to 39.91%:60.09% in 2019. For this reason, a new policy is needed to reduce the unemployment rate of vocational secondary school graduates in the form of a moratorium for vocational secondary school expansion, particularly in Java Island. If for some reason, there is a need to build new vocational secondary schools in a certain area, it must be based on demand-driven guided by labor market signals. More comprehensively, a policy shift is required to reduce the unemployment of graduates from secondary vocational schools.